2019
DOI: 10.1111/codi.14733
|View full text |Cite
|
Sign up to set email alerts
|

Discoid resection for colorectal endometriosis: results from a prospective cohort from two French tertiary referral centres

Abstract: Aim Using a prospective database of discoid resection performed in two tertiary referral centres, the aim of this study is to assess the feasibility, short‐term complication rates and clinical outcomes, including voiding dysfunction, of the procedure. Method A retrospective analysis of a prospective cohort database was conducted from February 2010 to October 2017 in two tertiary referral centres. One hundred and forty‐eight consecutive patients scheduled for colorectal endometriosis by discoid resection were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Furthermore, perioperative and postoperative complication rates are not elevated. The postoperative complication rates in our series are, as expected, lower than those reported by other experienced teams after laparoscopic management of colorectal endometriosis [23,28,35,36], but higher than in studies looking into endometriosis without rectal or urinary [37,38] involvement. These variable complication rates are related to different DIE lesion size, the severity and rate of additional resected lesions, and the technique adopted for colorectal DIE excision (shaving or discoid/segmental resection) [39].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Furthermore, perioperative and postoperative complication rates are not elevated. The postoperative complication rates in our series are, as expected, lower than those reported by other experienced teams after laparoscopic management of colorectal endometriosis [23,28,35,36], but higher than in studies looking into endometriosis without rectal or urinary [37,38] involvement. These variable complication rates are related to different DIE lesion size, the severity and rate of additional resected lesions, and the technique adopted for colorectal DIE excision (shaving or discoid/segmental resection) [39].…”
Section: Discussionsupporting
confidence: 64%
“…The major difficulty of comparing postoperative voiding dysfunction rates in different studies lies in the lack of a unanimous definition of the concept, variously described as urinary retention, bladder atony, voiding dysfunction calling for intermittent bladder catheterization (7 days postoperatively) [20,23], and the lack of consensus about what constitutes a normal/abnormal PVR [24−26]. Similarly, the definition of "transitory" voiding dysfunction differs and may refer to selfÀcatheterization of less than 30 days or 6 weeks, between 3 weeks and 6 months, and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIFU thus appears to be a safe, minimally invasive transrectal approach. Comparatively, in a longitudinal study involving 364 gastrointestinal surgical procedures, Abo et al (2019) encountered a 14.8% rate of Grade III complications, including 3.8% cases of RVF ( Abo et al , 2019 ). More recently, a meta-analysis by Bendifallah et al (2021) found a 1.5% rate of RVF, of which 0.3% occurred following rectal shaving, pointing to the safety of that approach.…”
Section: Discussionmentioning
confidence: 99%
“…The prospective data analysis of patients who underwent discoid resection in two endometriosis reference centers revealed good short-term results and low complication rates. According to the authors, the average size of the lesions was 30 mm (7 to 70 mm) (50) . Despite the possibility, after a disc resection, of the margins being compromised in up to 40% of cases (51) , there are few prospective and controlled studies comparing the technique with segmental resection in regard to late postoperative period, quality of life, travenously both intraoperatively and postoperatively, for 24 hours.…”
Section: Discoid Resectionmentioning
confidence: 99%